The Potential to Replace Cement with Nano-Calcium Carbonate and Natural Pozzolans in Cemented Mine Backfill - Mohammed Hefni; Maaz A. Ali (Advances in Civil Engineering)
The effectiveness of mine backfilling depends on the properties of its constituents. The high cost of cement, which is commonly used as a binder in mine backfill, has led researchers to seek alternatives to partially replace it with other binders. This study investigated the potential to use nano-calcium carbonate (NCC) and natural pozzolans (zeolite and pumice) along with Portland cement (PC) in mine backfill. Two types of experimental samples were prepared: (1) gold tailings and silica sand to investigate the effect of NCC and (2) nickel tailings to investigate the effect of natural pozzolans. The unconfined compressive strength (UCS) was measured for samples cured for up to 56 days. Moreover, selected samples were subject to mercury intrusion porosimetry to investigate microstructural properties. Results show that addition of NCC did not improve the UCS of backfill prepared with gold tailings and cured for 28 days, whereas a dosage of 1% NCC in backfill samples prepared with silica sand improved UCS by 20%, suggesting that the gold tailings negatively affected strength development. Natural pozzolans, in particular, 20% zeolite, had 24% higher UCS after 56 days of curing compared to samples prepared with PC and thus have the potential to partially replace cement in mine backfill.